Improving Performance of Wet-Gas Separator Through Compact Supersonic Vertical Configuration - AHMAD, MOHD FADZIL ALI (2018)
The natural gas energy stood the highest consumption in Malaysia where 36 648 ktoe have been utilized in 2012 compared to other sources of energies. The presence of free water have caused low quality output of natural gas